2021
DOI: 10.1186/s12052-021-00155-x
|View full text |Cite
|
Sign up to set email alerts
|

Role models, compatibility, and knowledge lead to increased evolution acceptance

Abstract: Background Evolution acceptance is still low in the United States, especially among religious students. Due to low acceptance, researchers have used a wide variety of methods to increase evolution acceptance. Six culturally competent methods for teaching evolution to religious students have been identified, this manuscript looks specifically at the method of reconciliation between religion and evolution. The reconciliation module has been shown to effectively increase evolution acceptance while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In the intervention, we focused on the cognitive aspects of learning (instead of emotional‐motivational factors such as acceptance of evolution) because (1) cognitive biases impact understanding in different domains of science, and thus dealing with them is of general relevance to science education (and not just evolution education) and (2) cognitive obstacles seem to be of higher relevance than emotional obstacles in evolution learning in Germany since acceptance of evolution is moderate to high. However, future studies may also investigate the effects of the interventional approaches on students' acceptance of evolution and perceived conflict (especially in populations with lower acceptance), and evolution instruction may additionally include sequences that explicitly address students' attitudes toward evolution and a potentially perceived conflict (Barnes & Brownell, 2017; Barnes, Elser, & Brownell, 2017; Ferguson & Jensen, 2021; Scharmann & Grauer, 2020; Truong et al, 2018). However, this was beyond the scope of the current study, and we do not consider the investigated instructional approaches as substitutes but as supplements to other approaches (e.g., addressing emotional‐motivational aspects and teaching subject‐specific knowledge).…”
Section: Discussionmentioning
confidence: 99%
“…In the intervention, we focused on the cognitive aspects of learning (instead of emotional‐motivational factors such as acceptance of evolution) because (1) cognitive biases impact understanding in different domains of science, and thus dealing with them is of general relevance to science education (and not just evolution education) and (2) cognitive obstacles seem to be of higher relevance than emotional obstacles in evolution learning in Germany since acceptance of evolution is moderate to high. However, future studies may also investigate the effects of the interventional approaches on students' acceptance of evolution and perceived conflict (especially in populations with lower acceptance), and evolution instruction may additionally include sequences that explicitly address students' attitudes toward evolution and a potentially perceived conflict (Barnes & Brownell, 2017; Barnes, Elser, & Brownell, 2017; Ferguson & Jensen, 2021; Scharmann & Grauer, 2020; Truong et al, 2018). However, this was beyond the scope of the current study, and we do not consider the investigated instructional approaches as substitutes but as supplements to other approaches (e.g., addressing emotional‐motivational aspects and teaching subject‐specific knowledge).…”
Section: Discussionmentioning
confidence: 99%
“…25 These findings are in line with other current research that has shown positive role models are an important part of helping students change their minds and accept other controversial biological concepts, like evolution. 26,27 Students have stated that professors who demonstrate their own ability to reconcile help students to reconcile their own religiosity with evolution. These students found their professors to be relatable examples to follow in reconciliation.…”
Section: Discussionmentioning
confidence: 99%
“…As religious people tend to rely on tradition, the participants suggested to mention various Jewish leaders that accept evolution, or religious scientists that can be seen as role models (seventh practice). Ferguson and Jensen (2021) found that one of the factors students mentioned as reasons for a change towards evolution acceptance was the presence of a role model. In another study, once students saw someone who reconciled evolution and religion, the conflict they felt with evolution decreased (Holt et al 2018).…”
Section: T7mentioning
confidence: 99%